Sustainability perspectives for future continuity of mushroom production: The bright and dark sides - Okuda, Yasuhito (Frontiers in Sustainable Food Systems, 2022)
Mushrooms are now well-known as healthy food ingredients that contain dietary fiber, vitamin D and compounds with numerous health benefits. Its procurement was initially based on the collection of naturally occurring wild mushrooms in the field, which depended on the region. Modern established cultivation techniques have contributed to environmental sustainability through the recycling of forestry and agricultural by-products and have successfully developed into a global industry. Such development of global mushroom production is the “bright” side as circular agriculture. However, the potential environmental and economic benefits in the sustainability of mushroom production have not yet been widely recognized, and its global production trend has stagnated in recent years. Therefore, dissemination activities through international mutual cooperation centered on education including ecology, cultivation science, and nutrition science of mushrooms are indispensable for the development of mushroom production in the future. On the other hand, we also need to urgently identify and address the challenges associated with negative sustainability impacts, or “dark” side, of mushroom production. The adverse effects of spores derived from cultivated mushrooms on the surrounding environment and disposal methods such as used heat-resistant bags and spent mushroom substrates are often neglected. Clarifying such the positive and negative aspects of sustainability in mushroom production and presenting their future prospects should contribute to improving international perceived value and the continuity of mushroom production.